Effects of tree leaf forage supplementation on rumen fermentation and microbial profile of goats - Adewale, Ahmed Muideen (2016)
Increase in the cost of livestock production with the use of conventional feed is distressful, threatening the food security and livestock sustenance especially ruminant. Alternative to this is to diversify and quest for other source of feed such as forages which are inexpensive, high proximity and high nutritive value for animal optimum utilization. Hence, the purpose of the present study. In the first experiment, evaluation of nutritive and anti-nutritive factor of three selected tree forages (Kleinhovia hospita, Leucaena leucocephala and Gliricidia sepium) and their effect on the in vitro rumen fermentation were investigated. The proximate analysis was determined by AOAC procedure, in vitro cumulative gas production using Ørskov and McDonald model, metabolizable energy determined by Menke and Steingass equation method and rumen fermentation by gas chromatography. The crude protein (CP) of the forages (19%, 23.3% and 20.8% respectively) were more than the 12% CP requirement of ruminant. The NDF and ADF which to some extent dictate the feed intake and the digestibility respectively was found to be lower in KH compared to LL and GS. The lower value is an indication of higher feed intake and digestibility. In the in vitro study, the net gas production (NGP), in vitro dry matter digestibility and metabolizable energy was also high in KH than LL and GS. Furthermore, the result from the in vitro rumen fermentation indicated that the total volatile fatty acid (TVFA) was significantly different (P<0.05) among the forages with KH having the highest followed by LL and GS. There was no significant difference among the forages in the acetic acid concentration. The propionic concentration in KH was higher compared to LL and GS while the concentration of butyric acid and AP ratio in KH was the lowest followed by LL and GS. This shows better utilization of dietary component of KH than others. In the second experiment, KH and LL were selected from the result of the first experiment to formulate diet for the feeding trial of four fistulated Boer male goat in a ii 4X4 Latin square design. The experiment was made up of four dietary treatments which were: Diet 1 was made up of only concentrate, Diet 2 with inclusion of KH, Diet 3 with inclusion of LL and Diet 4 with mixture of KH and LL (KHLL). The effect of the dietary treatment with sampling time (0, 2, 4, 6 and 12 h) on rumen fermentation and microbial profile were investigated. The rumen fermentation result shows a fluctuation of the dietary treatment with sampling time. The TVFA among the dietary treatments were not significantly different (P>0.05) at 12 h postprandial but the propionic acid concentration were significantly different among the dietary treatments with KHLL having the highest concentration followed by KH, LL and control. In the butyric acid concentration at 12 h postprandial, the control, KH and LL were similar and significantly different (P<0.05) from KHLL which recorded the lowest butyric acid concentration and this was a confirmation of the efficient utilization of the dietary energy. In the concentration of acetic acid, the level was noted to increase until 4 h postprandial before gradual decline with the KHLL recorded to be higher (P<0.05) than the rest. Similarly, the NH3 concentration of KHLL is significantly different (P<0.05) from other diets which were similar. From the in vivo microbial population profile result, the total bacteria were noted to be at the peak of their population at 4 h postprandial before gradual decline in all treatment diets. At 12 h postprandial, the total protozoa and methanogens were found decreasing with sampling time and the forage inclusion diets (KHLL, KH and LL) were significantly lower (P<0.05) than the control. The number of cellulolytic bacteria R. albus, R. flavefaciens and Fibrobacter succinogenes were more in the forage inclusion diet than the control at 4 h postprandial. Based on the outcome of the present study, it can be concluded that the KHLL inclusion diet could be efficiently used in goat diet without compromising the nutrient potential by reducing the methanogen and protozoa numbers, enhancing propionic acid, acetic acid and nutrient utilization. In addition, acetate is essential in the formation of milk fat and propionate aid the synthesis lactose (milk sugar) as well as increase milk yields in dairy animals.